Five transition pathways to renewable energy futures—scenarios from a Delphi study on key drivers and policy options - Rikkonen Pasi; Lauttamäki Ville; Parkkinen Marjukka; Varho Vilja; Tapio Petri (Springer, 2022)
At many levels of society—in regions, corporations, and among citizens—awareness is increasing, and actions towards more sustainable energy are being taken. The key drivers of this transition have been climate change, the scarcity of resources, and environmental consciousness. The speed of change and its impacts on the energy system transition are still unknown. It is therefore important to anticipate probable, preferable, or avoidable future paths that will contribute to the discussion of the direction and conditions of such futures. In this article, five energy scenarios are presented for Finland until 2030. The scenarios are based on a two-round Delphi application, in which energy experts were first interviewed and then a survey phase was conducted. We used cluster analysis to construct the scenarios and arranged the responses to open-ended questions as narratives to deepen the scenarios. Based on the cluster analysis, five clusters were constructed, namely, (1) business as usual, (2) energy saving and decarbonisation, (3) climate-friendly transformation, (4) green growth, and (5) degrowth. These scenarios illustrate how varying sets of drivers of change in society, and a set of energy policy measures, are connected with energy futures. Expert information thus organised can be used to advise policymakers when designing future climate and energy policy.